Fading of a novel colorimetric receptor after recognizing H2PO4−. Issue 8 (3rd August 2018) - Li, Dan; Zheng, Shibing; Lin, Huakuan; Yang, Zhongyue; Huang, Weiwei
Abstract: A novel selective and sensitive colorimetric receptor1 ( 1, 10 - phenanthroline - 2, 9 - dialdehyde bis -(- p - nitrophenylureasemicarbo - hydrazone )) based on urea showing distinctive color fading phenomenon towards H2 PO4 − ion was reported. Fancifully, the recognition process of receptor1 to H2 PO4 − was not interfered by the existence of others anions. We have probed the binding mechanism of1 -H2 PO4 − that H2 PO4 − ion induced competitive hydrogen binding process via intramolecular hydrogen-bond by UV–vis, fluorescence, 1 H NMR titrations and ESI-MS experiments. Abstract :